2009
DOI: 10.1021/cm901293e
|View full text |Cite
|
Sign up to set email alerts
|

Self-Polymerization of Dopamine as a Versatile and Robust Technique to Prepare Polymer Capsules

Abstract: Stable polydopamine capsules are prepared by the single-step deposition and self-polymerization of dopamine onto a range of colloidal silica template particles with different sizes and porosities. MTT assays reveal negligible cytotoxicity of the capsules toward cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
360
0
3

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 468 publications
(372 citation statements)
references
References 30 publications
9
360
0
3
Order By: Relevance
“…7a). This result is in good agreement with the previously reported negligible cytotoxicity of PDA capsules to LIM1215 cells [20].…”
Section: Interaction Of Pda Coated Liposomes With Myoblast Cellssupporting
confidence: 93%
See 1 more Smart Citation
“…7a). This result is in good agreement with the previously reported negligible cytotoxicity of PDA capsules to LIM1215 cells [20].…”
Section: Interaction Of Pda Coated Liposomes With Myoblast Cellssupporting
confidence: 93%
“…as matrix polymer for molecular imprinting [18], and for life cell encapsulation [19]. PDA capsules have been considered using particles [20][21][22][23] or oil emulsion droplets [24] as templates. Although cargo loading in PDA capsules has been shown, no impact on the cell viability due to the presence of the cargo has been reported and only the absence of inherent cytotoxicity has been demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, several recent studies from pioneering groups in the LbL field report on novel strategies that dramatically reduce the amount of batch operations while till aiming to mimic as much as possible the highly versatile concept of LbL technology. [104][105][106] Taking into account the above mentioned considerations we are convinced that there is a bright future for polymeric multilayer capsules, providing that several important issues are being addressed the coming decade.…”
Section: Discussionmentioning
confidence: 99%
“…Toxicity of the PDA is an important property when they are planned to be used as drug delivery vehicles. Studies have demonstrated that PDA did not hinder the viability or proliferation of many kinds of mammalian cells such as fibroblasts, osteoblasts, neurons, endothelial cells [11], and colon cancer LIM1215 cells [12]. In vivo study showed that Ag @ PDA NCs were stable within cells of the liver and spleen for at least six weeks, and Ag @ PDA NCs did not show notable histological toxicity to main organs of mice in a long time [13].…”
Section: Pda Capsules and Nps As Carriers For Drug Deliverymentioning
confidence: 98%